Moral disengagement and individual differences in cannabis use: investigating perspectives of effective intervention in adults - Mbewe, F.P. (2017)
Despite the illicit nature and association of cannabis, it is still the most commonly used illegal drug in the UK. To use the substance, individuals may selectively disengage their moral agency and associated guilt through Bandura’s Mechanisms of MD (2002). This paper investigates the influence of brief intervention on adult cannabis use, exploring participants’ attitudes and behavioural beliefs (ABB), intentions, and the mechanisms of Moral Disengagement (MD). To test whether it is possible to reinstate moral agency, participants experienced a brief (2-3 minutes) intervention-style manipulation to explore four conditions. This comprised one of three targeted psychoeducational manipulation on cannabis use (hedonic, health and criminal effects), as well as a control stimulus. In an experimental design, 176 participants completed self-report surveys on ABB of perceived control and behavioural intention, along with MD and antecedent personality and impulsivity dimensions. Following exposure to a video clip, participants were retested on ABB and MD. Retest questionnaires found significant reductions in ABB, including behavioural intention to use cannabis after both health and hedonic approaches to education, in comparison to the control condition. MD significantly correlated with a participant’s behavioural intention to use cannabis in the future. Findings offer implications for brief intervention strategies with cannabis users. These results suggest that individuals who are more likely to show intention to use cannabis in the future, use MD to reduce self-censure, but that associated attitudes that facilitate MD can be manipulated. Crime-targeted intervention appeared less effective in reducing pro-cannabis ABB, likely due to increased social norms of cannabis use amongst consumers. Such findings are mirrored in current debates in legislation.